Clinical presentation of post-COVID pain and its impact on quality of life in long COVID patients: a cross-sectional household survey of SARS-CoV-2 cases in Bangladesh - Md. Feroz Kabir; Khin Nyein Yin; Mohammad Saffree Jeffree; Fatimah Ahmedy; Muhamad Faizal Zainudin; Ohnmar Htwe; Sharmila Jahan; Md. Zahid Hossain; K. M. Amran Hossain; Tofajjal Hossain; Iqbal Kabir Jahid; Sonjit Kumar Chakrovorty (Springer Nature, 2024)
Background Pain is one of the prevalent Long COVID Symptoms (LCS). Pain interferes with the quality of life (QoL) and induces disease burden. Purpose The study aimed to elicit the clinical presentation of pain and determine the relationships between QoL and pain in LCS. Methods This household cross-sectional study of 12,925 SARS-CoV-2 cases between July and December 2021 was carried out in eight administrative divisions of Bangladesh. Stratifed random sampling from the cases retrieved from the Ministry of Health was employed. Symptom screening was performed through COVID-19 Yorkshire Rehabilitation Scale, and long COVID was diagnosed according to World Health Organization (WHO) criteria. The analyses were conducted using IBM SPSS (Version 20.00). Results The prevalence of pain in long COVID was between 01 and 3.1% in the studied population. The study also found fve categories of pain symptoms as LCS in Bangladesh: muscle pain 3.1% (95% CI; 2.4–3.8), chest pain 2.4% (95% CI; 1.8–3.1), joint pain 2.8% (95% CI; 2.2–2.3), headache 3.1% (95% CI; 2.4–3.8), and abdominal pain 0.3% (95% CI; 0.01–0.5). People with LCS as pain, multiple LCS, and longer duration of LCS had signifcantly lower quality of life across all domains of the WHOQOL-BREF (P<0.001) compared to asymptomatic cases. Conclusion Three out of ten people with long COVID experience painful symptoms, which can signifcantly reduce their quality of life. Comprehensive rehabilitation can improve the symptoms and reduce the burden of the disease.